Analisis Akuntabilitas Dan Transparansi Tentang Pengelolaan Pendapatan di Objek Wisata Goa Gajah - Dewa Ayu Radela; Sang Ayu Putu Arie Indraswarawati; I Made Endra Lesmana Putra (UNHI Press, 2026)
The importance of accountability and transparency in public sector financial management, particularly in tourist attractions that contribute significantly to the regional economy. The purpose of this study was to analyze the accountability and transparency practices in revenue management at the Goa Gajah tourist attraction in Gianyar. This study used a qualitative approach with a descriptive method through a case study, involving interviews, observations, and documentation with managers, village officials, and beneficiary communities. The results showed that accountability has been realized through daily recording of revenue and the number of visits submitted to the Gianyar Regency Tourism Office, accompanied by a revenue sharing mechanism of 60% for the office and 40% for the Bedulu Traditional Village. Community participation occurs in the form of economic roles, such as traders and tour guides, as well as the receipt of revenue information through annual village meetings. Transparency is expressed in the timely delivery of revenue data, clear, accurate, and accessible, although details of fund use are not always disclosed openly and require special requests. In conclusion, revenue management at Goa Gajah has met the principles of accountability and transparency in general, but needs to be improved in the detailed reporting of fund use. The implication is that this practice can be a model for the management of other tourist attractions in building public trust and ensuring that there is no good governance-based management.